The superhelical density of nuclear DNA from human cells. - Cook, P; Brazell, I (1977)
Structures resembling nuclei may be released by gently lysing human cells in solutions containing non-ionic detergents and high concentrations of salt. These structures, which we call nucleoids, sediment in sucrose gradients containing the intercalating agent, actinomycin D, in the manner characteristic of superhelical DNA. We have determined the concentration of actinomycin that minimises the rate of sedimentation of nucleoids. At this concentration, we have determined the amount of drug bound per base pair of DNA by means of a double-labelling procedure. Assuming that each molecule of actinomycin bound to nucleoid DNA unwinds the double helix by 26 degrees, we calculate that there is one supercoil every 90-180 base pairs in nucleoid DNA. These values lie within the range found for the circular DNA molecules of plasmids and viruses.